A Corpus-based syntactic error analysis of Japanese learners' writing in Lembaga Pelatihan Kerja (LPK) Cahaya Mandiri Indonesia - Prihantoro; Kautsar, Haqi Sang; Kharismi, Annisa; Nuradita, Rizki Dwi; Cahyaningtyas, Puspita Luruh (Japanese Research on Linguistics, Literature, and Culture, 2024)
This study investigates the predominant frequency of syntactic errors in written compositions by Japanese language learners at Lembaga Pelatihan Kerja (LPK) Cahaya Mandiri Indonesia. It explores the correlation between these errors and the learners' educational duration. The dataset consists of compositions by students who have completed Japanese language job interviews. Using a corpus-based analysis, the study reveals that the most frequent syntactic errors among these learners involve simple sentence errors (KT), comprising 24.4% of total errors. These errors are most common among students with 4 months of learning (41.3% of errors) and 5 months of learning (20.4%). However, for students with 6 months of learning, verb phrase errors (FV) become more prominent, making up 31.7% of errors. A correlation is found between the type of syntactic errors and the duration of language learning. This includes a positive correlation in errors related to adverbial phrases (FD), adjective phrases (FA), and independent clauses (LB), and a negative correlation in errors related to compound sentences (KM) and final particles (PA). Additionally, varying correlations are observed across categories such as single sentences (KT), verb phrases (FV), case particles (PK), noun phrases (FN), conjunction particles (PO), and compound sentences (KS)